Square planar cobalt(II) hydride versus t-shaped cobalt(I): structural characterization and dihydrogen activation with PNP-cobalt pincer complexes - Merz, Lukas; Blasius, Clemens K.; Wadepohl, Hubert; Gade, Lutz H. (Inorganic chemistry, 2019)
The carbazole-based pincer ligand R(CbzPNP)H (R = iPr, tBu) has been used for the synthesis and characterization of various low- and high-spin cobalt complexes. Upon treatment of the high-spin complexes R(CbzPNP)CoCl (2R-CoIICl) with NaHBEt3, the selective formation of cobalt(II) hydride 3iPr-CoIIH and T-shaped cobalt(I) complex 4tBu-CoI was observed, depending on the substituents at the phosphorus atoms. For an unambiguous characterization of the reaction products, a density functional theory (DFT) supported paramagnetic NMR analysis was carried out, which established the electron configuration and the oxidation states of the metal atoms, thus demonstrating the significant impact of ligand substitution on the outcome of the reaction. A distinct one-electron reactivity was found for 4tBu-CoI in the dehalogenation of tBuCl and cleavage of PhSSPh. On the other hand, the CoI species displayed two-electron redox behavior in the oxidative addition of dihydrogen. The resulting dihydride complex 6tBu-CoIII(H)2 was found to display sluggish reactivity toward alkenes, whereas the cobalt(II) hydride 3iPr-CoIIH was successfully employed in the catalytic hydrogenation of unhindered alkenes. The stoichiometric hydrogenolysis of 8iPr-CoIIBn at elevated pressure (10 bar) led to a rapid cleavage of the Co-C bond to yield hydride complex 3iPr-CoIIH. On the other hand, treatment of 2iPr-CoIICl with phenethylmagnesium chloride directly resulted in the formation of 3iPr-CoIIH, indicating facile β-H elimination of the alkene insertion product (reversibly) generated in the catalytic hydrogenation. On the basis of these observations, a mechanistic pathway involving a key σ-bond metathesis step of the CoII-alkyl species is proposed.